Post-harvest processed parsnip showed improved anti-oxidative capacity and protective potential against acrolein-induced inflammation in vitro and in vivo - Lee, Kangwook; Pan, Jeong Hoon; Choi, La Yoon; Ju, Jaehyun; Le, Brandy; Williams, Liana C.; Cho, Tae Jin; Lee, Eunjin; Yoon, Ji Soo; Park, Chae Lee; Kim, Sang-Yoon; Yeon, Sung Hum; et al. (Frontiers in Nutrition, 2024)
Introduction Post-harvest processing plays a crucial role in enhancing the bioactive properties of vegetables. This study aimed to investigate the impact of post-harvest aging on parsnip’s bioactive profile and its protective effects against acrolein (Acr)-induced inflammation, a common pollutant and irritant linked to respiratory inflammation. Methods Parsnips (Pastinaca sativa L.) were aged at 60°C for up to 30 days, with extracts collected at intervals. Total phenolic content (TPC) and antioxidant capacity were assessed using DPPH assays. Key bioactive compounds, including falcarindiol, DDMP, and 5-HMF, were quantified. In vitro studies used BEAS-2B cells to evaluate anti-inflammatory effects, while in vivo tests involved treating Acr-exposed mice with aged parsnip extract to observe cytokine responses. Results Aged parsnip extracts showed a 9.96-fold increase in TPC and a 4.25-fold increase in antioxidant capacity after 30 days. Bioactive compounds significantly increased in aged samples, especially falcarindiol and 5-HMF. In vitro, aged parsnip reduced Acr-induced TNF-α and IL-1β expression. In vivo, treated mice showed reduced bronchial inflammation, goblet cell hyperplasia, and cytokine expression compared to controls. Discussion These findings suggest that post-harvest aging enhances parsnip’s antioxidant and anti-inflammatory properties, highlighting its potential as a functional food ingredient for managing inflammation and respiratory health.